CAPACITY BUILDING CIVITAS ACADEMIKA FIS UNNES (Harmony: Jurnal Pembelajaran IPS dan PKN, 2018)
Along with the demands of internationalization within the Semarang State University, there needs to be a leap of movement from all elements within it such as students, lecturers and education staff. Of course, aspects of HR both in terms of quantity and quality can be seen in terms of knowledge, skills, and attitude. Based on the results of community service activities, the conclusions from this PPM activity are: Activities to increase Capacity Building for the academic community of the Faculty of Social Sciences can improve: Skills in "solving problems" and "decision making" quickly and right based on skills in identifying "key problems"; Improve ability in "leadership and empowerment" (situational leadership & empowerment) that is tailored to the situation; and become an effective and efficient "agent of change" (change agent) in their respective work units. Based on the results and discussion above, the suggestions from community service activities are: There needs to be continuous activities from the Faculty of Social Sciences so that the interests and talents of the Faculty of Social Sciences academics can be well accommodated and can be practiced in community life. Seiring dengan tuntutan internasionalisasi dilingkungan Universitas Negeri Semarang, perlu adanya loncatan gerakan dari semua unsur elemen didalamnya seperti mahasiswa, dosen dan tenaga kependidikan. Tentunya, aspek SDM baik dari sisi kuantitas maupun kualitas dapat dilihat dari sisi knowledge, skill, dan attitude. Berdasarkan hasil kegiatan pengabdian pada masyarakat, maka simpulan dari kegiatan PPM ini adalah: Kegiatan peningkatan Capacity Building bagi civitas akademika Fakultas Ilmu Sosial dapat meningkatkan: Keterampilan dalam â€œmenyelesaikan masalahâ€ (problem solving) dan â€œpengambilan keputusanâ€ (decision making) secara cepat dan tepat didasarkan pada kecakapan dalam mengidentifikasi â€œkey problemâ€; Meningkatkan kemampuan dalam â€œkememimpinan dan pemberdayaanâ€ (situational leadership & empowerment) yang disesuaikan dengan situasi; dan menjadi â€œagen perubahanâ€ (change agent) yang efektif dan efisien di lingkungan unit kerja masing-masing. Berdasarkan hasil dan pembahsan di atas maka saran dari kegiatan pengabdian pada masyarakat, ini adalah: Perlu adanya kegiatan yang kontinu dari pihak Fakultas Ilmu Sosial agar minat dan bakat dari para akademisi Fakultas Ilmu Sosial dapat terakomodir dengan baik dan dapat dipraktikan dalam kehidupan bermasyarakat.